Greece : Ex Post Evaluation of Exceptional Access Under the 2010 Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
Greece adopted an ambitious program to eliminate fiscal and current account imbalances, regain competitiveness, maintain financial stability, and boost growth and employment. While significant fiscal adjustment occurred, critical objectives such as regaining confidence and restoring growth were not achieved. The program lacked in better tailoring of IMF lending policies, avoiding undue delays in debt restructuring, attention to the political economy of adjustment, and parsimony in fiscal structural reforms. The importance of streamlining the Troika process and effective risk-sharing arrangements within the euro area has been stressed by Executive Directors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet